Cure and performance of castor oil polyurethane adhesive. (December 2019) - Gama, Nuno; Ferreira, Artur; Barros-Timmons, Ana
Abstract: Aiming at the development of sustainable materials, in this study, a biobased wood polyurethane adhesive (PUA), derived from castor oil (CO), was synthetized and its properties were compared with a conventional wood adhesive. Different NCO/OH ratios have been used to assess its effect on the properties of the ensuing adhesives. FTIR, and DMA were used to monitor the extent of reaction and the glass transition temperature of the adhesive, respectively. In turn, the wood bonding properties of the PUA over time were assessed by lap shear using pine wood specimens. Is was observed that the lap shear strength increases with the increase of the R NCO/OH up to R NCO/OH  = 2.50. Above this ratio, the adhesive performance decreases slightly, due to the rigidity of the PUA. Comparison with a conventional wood adhesive showed that CO derived adhesives presented similar strength properties but required less time to develop the ultimate bonding strength. The chemical and thermal stability of the most promising CO adhesive was also assessed. Despite of being sensitive to the chemical environment, the castor oil derived adhesives presented higher thermal stability than conventional wood adhesives. Finally, the cure process of CO derived adhesives was studied by differential scanning calorimetry and the Kissinger and Ozawa methods were used to determine the activation energy (Ea). The former afforded a value for Ea = 80.55 and the latter Ea = 87.07 kJ mol −1 . Moreover, it was observed that the activation energy is dependent on the degree of cure, increasing slightly up to 0.6 and decreasing significantly afterwards.